Pediatric Microbial Keratitis in Queensland, Australia (2005 to 2015). Issue 12 (December 2019) - Green, Matthew; Apel, Andrew; Stapleton, Fiona
Abstract : Purpose: To estimate the incidence and define the demographic and microbiological profile of pediatric microbial keratitis (MK) in Queensland, Australia. Methods: This is a retrospective study based on the multicenter database of all patients with positive corneal scrapes in Queensland, Australia, between 2005 and 2015. Pathology organizations in Queensland were identified by online and local directory search and were requested to provide digital records of the corneal scrapes, including patient demographics and culture and antibiotic sensitivity results. Patient demographics, yearly incidence (based on state population data), cultured organisms, and antibiotic sensitivities in MK in patients 16 years old or younger with keratitis were reported and compared with adults. Results: Pediatric cases comprised 125 cases of a total 3182 (3.9%) included in the database. The yearly incidence of MK in children was estimated to be 0.11 cases per 10, 000 people 16 years old or younger (95% confidence interval, 0.086–0.134), which was significantly lower than the estimated incidence in people older than 16 years (0.82 per 10, 000 people; 95% confidence interval, 0.72–0.92; P < 0.0001). The average age of pediatric patients was 9.2 years (SD 5.5). Culture results showed Gram-positive organisms were the most common causative organisms (84%; 67.2%), Pseudomonas aeruginosa was the most common single organism (24%; 19.2%), and fungal recovery was low (4%; 3.2%). Cultures positive for Streptococcus pneumoniae (17%; 13.6%; P < 0.001) and bacteria sensitive to all recorded antibiotics (96.8%; P < 0.001) were significantly more common in children. Conclusions: MK in pediatric patients is less common than in adults. Although Streptococcus pneumoniae was more common in children, P. aeruginosa was the most common isolate.